2013
DOI: 10.5352/jls.2013.23.6.812
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reserpine on the Behavioral Defects, Aβ-42 Deposition and NGF Metabolism in Tg2576 Transgenic Mouse Model for Alzheimer's Disease

Abstract: Reserpine, an anti-hypertensive drug, is able to positively modulate several phenotypes associated with Aβ toxicity in a Caenorhabditis elegans model of Alzheimer's disease (AD). We investigated into the therapeutic effects of reserpine on mammalian neurodegenerative disorders, and found that significant alteration of the key factors influencing AD was detected in Tg2576 mice after reserpine treatment for 30 days. The aggressive behavior of Tg2576 mice was significantly improved upon reserpine treatment, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…More importantly, reserpine improved the cognition of the 5xFAD AD Tg mice at the age (Figure 1) where these mice are reported to show cognitive deficits. While our study was ongoing, Go et al [16] reported that reserpine can help relieve AD pathogenesis in Tg2576 mice through down regulation of Aβ 42 deposition, NGF secretion [16], but had not assessed cognitive function. Since decline in cognition is the most devastating feature of AD, here, we show that reserpine improves spatial working memory and delays cognitive deficits in the 5XFAD AD Tg mice at the low dosage of 0.08 mg that too administered only on alternate days which is in line with the low dosage of reserpine currently in use.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…More importantly, reserpine improved the cognition of the 5xFAD AD Tg mice at the age (Figure 1) where these mice are reported to show cognitive deficits. While our study was ongoing, Go et al [16] reported that reserpine can help relieve AD pathogenesis in Tg2576 mice through down regulation of Aβ 42 deposition, NGF secretion [16], but had not assessed cognitive function. Since decline in cognition is the most devastating feature of AD, here, we show that reserpine improves spatial working memory and delays cognitive deficits in the 5XFAD AD Tg mice at the low dosage of 0.08 mg that too administered only on alternate days which is in line with the low dosage of reserpine currently in use.…”
Section: Discussionmentioning
confidence: 93%
“…As reserpine modulates biogenic amines neurotransmitters, the secondary problems mentioned above also could be alleviated by it. Go et al [16], report that reserpine can significantly reduce the aggressive behavior in the Tg2576 AD mice. In Ayurvedic medicine, reserpine has been used as an antipsychotic and tranquilizer for more than a millennium.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations